2002
DOI: 10.1210/jc.2001-012056
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Decreases Plasma Total Homocysteine in Overweight Young Women with Polycystic Ovary Syndrome

Abstract: Women with polycystic ovary syndrome (PCOS) have a clustering of cardiovascular risk factors, such as obesity, lipid abnormalities, impaired glucose tolerance, insulin resistance, and hypertension. Exercise is reported to lower the incidence of cardiac events. The effect of exercise on plasma homocysteine concentrations, an independent cardiovascular risk factor, has not been previously reported in women with PCOS. We examined the effects of exercise on plasma total homocysteine concentrations in young overwei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
147
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(158 citation statements)
references
References 53 publications
5
147
0
6
Order By: Relevance
“…Folate, vitamin B 12 and B 6 are involved in the transsulfuration pathway and vitamin B 6 participates in the remethylation reaction [6] (Figure 1). The enzyme methionine synthase is involved in the remethylation reaction and conversion of homocysteine to methionine requires both folate and vitamin B 12 as coenzymes [7]. Moreover, vitamin B 6 acts as a coenzyme for the enzymes cystathionine-β-synthase and cystathionine-γ-lyase in the transsulfuration pathway to convert homocysteine to cysteine.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Folate, vitamin B 12 and B 6 are involved in the transsulfuration pathway and vitamin B 6 participates in the remethylation reaction [6] (Figure 1). The enzyme methionine synthase is involved in the remethylation reaction and conversion of homocysteine to methionine requires both folate and vitamin B 12 as coenzymes [7]. Moreover, vitamin B 6 acts as a coenzyme for the enzymes cystathionine-β-synthase and cystathionine-γ-lyase in the transsulfuration pathway to convert homocysteine to cysteine.…”
Section: Introductionmentioning
confidence: 99%
“…But there is also a huge variety in the methodology applied among all the studies, hence, there is difficulty to reach an agreement [5]. Some researchers have demonstrated reduced tHcy concentrations after a training period [12,13]; others have related high PA levels and cardiorespiratory fitness with lower homocysteine concentrations [14,15]. In contrast, some studies have shown higher tHcy concentrations after acute exercise, training period or after a specific sport competition [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…owing in large part to the variations in study design and exercise regimes [7][8][9][10][11][12][13][14][15]. Moreover, 82 discrepancies within these human studies, including B-vitamin and subject training status, as 83 well as variations in mode, intensity, and duration of test exercises, limit the strength of their 84 conclusions [16,17].…”
mentioning
confidence: 99%
“…The dyslipidemia of PCOS is characterized by elevated plasma levels of cholesterol, low density lipoproteins (LDL), very low density lipoproteins (VLDL), and triglycerides with concomitantly reduced concentrations of high density lipoproteins (HDL) [52][53][54][55] . Homocysteine levels are also higher in women with PCOS compared to controls [56][57][58][59] , and hyperhomocysteinemia represents another independent risk factor for the development of cardiovascular disease 60 . Moderate hyperhomocysteinemia predisposes individuals to endothelial dysfunction via a mechanism involving increased oxidative stress 61 .…”
Section: Cardiovascular Risksmentioning
confidence: 99%